The multifrequency low-voltage plasma-beam generator - Antipov, V.S.; Arhipov, A.V.; Bez’yazychny, I.A.; Berezhnaya, I.V.; Kornilov, E.A. (Вопросы атомной науки и техники, 2007)
The authors have submitted the experimental results concerning the excitation of multi-frequency oscillations in the beam-plasma generator based on the helical slow-wave structure. It is demonstrated that oscillations can be excited under the beam current up to 4 A, the accelerating voltage being up to 4 kV at several frequencies within the range 0.6‑1.2 GHz in the quasi-continuous and continuous regimes. Представлено експериментальні результати по збудженню багаточастотних коливань у пучково-плазмовому генераторі на основі спіральної уповільнюючої структури. Продемонстровано можливість збудження коливань при струмі пучка до 4 А, прискорюючій напрузі до 4 кВ на декількох частотах у діапазоні 0,4-1,2 ГГц у квазінеперервному та неперервному режимах. Представлены экспериментальные результаты по возбуждению многочастотных колебаний в пучково-плазменном генераторе на основе спиральной замедляющей структуры. Продемонстрирована возможность возбуждения колебаний при токе пучка до 4 А, ускоряющем напряжении до 4 кВ на нескольких частотах в диапазоне 0,4-1,2 ГГц в квазинепрерывном и непрерывном режимах.